It's a-- it's a-- it's a mitzvah! - Heiman, Diane (Jewish Lights Publishing, 2012)
This lively picture book for children ages 3-6 is filled with amiable animals, who through their actions demonstrate age-appropriate mitzvot, including welcoming new friends, forgiving mistakes, respecting elders, and sharing food with the hungry. It engages children through playful illustrations; likeable animal characters, including Mitzvah Meerkat, the narrator; humor and the repetition of the fun-to-say phrase "It's a ... it's a ...it's a mitzvah!" that encourages children to chime in as the words are repeated throughout the book. Side notes on each spread explain the specific mitzvah in every vignette.--Publisher.